Analisis Percaya Diri Anak Usia Dini Di TK Negeri Pembina Kecamatan Kota Utara Kota Gorontalo - Maghfira R. Mustapa; Maryam Bilale; Tri Sela Lauding; Fiola Indah Putri Pratama (Institut Nalanda, 2024)
Building self-confidence in children is very important because it helps children to be more independent and is the basis for children's social, emotional, and academic development in the future. The research aims to determine the role of teachers in developing children's self-confidence. At the time of conducting the research, there were 18 children, some of whom still lacked self-confidence. This research method uses a qualitative descriptive method where the collection method uses data based on what happens in the field, namely in the form of observation results. From the research results above, it was found that in Pembina Kota Utara Kindergarten class 1A, emotional development, especially in the aspect of self-confidence, was still low. Where the child does not show indicators of self-love, in the self-love section the child is not yet able to introduce himself and in the indicator section of trying new things the child does not dare to appear in public